Provoked in Venice - Rudman, Mark (Wesleyan University Press ; University Press of New England, 1999)
The remarkable third volume in a trilogy that includes the award-winning Rider and Millennium Hotel.
Keywords: Venice (Italy) -- Poetry.; POETRY -- American -- General.; Italy -- Venice; Poetry